ANALISIS PERBEDAAN TINGKAT PEMAHAMAN MAHASISWA AKUNTANSI TERHADAP MATA KULIAH AUDITING 1 (Studi Empiris pada Mahasiswa Program Studi Akuntansi S 1 Universitas Bengkulu, Universitas Muhammadiyah Bengkulu) - Krenawati - (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2016)
The purpose of this study is to prove and analyze whether there is a difference understanding toward auditing 1 material between Accounting students of University of Bengkulu (UNIB) and the Accounting students of Muhammadiyah University of Bengkulu (UMB). This study used primary data, and analyzed by using the Independent Sample t Test. Based on calculations, it is known that there is significant difference of students’ understanding toward Auditing 1 course between students of Accounting Study Program Economic Faculty of UNIB and Accounting Study Program students of UMB, where the level of students’ understanding of Accounting Study Program Economic Faculty of UNIB is proved better than the Accounting students Economic Faculty of UMB.  Key words: Auditing 1 Understanding, UNIB, UMB